In Community Rehabilitation Programme PPDK Implementation Visit - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 26 January 2023 - Universiti Malaysia Pahang (UMP) received a visit from a delegation from the Ministry of Higher Education (MOHE), Ministry of Finance of Malaysia and Department of Social Welfare (JKM) to review the implementation of the In-Community Rehabilitation Programme (PPDK) at the UMP level.